2021
DOI: 10.1016/j.athoracsur.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Morbidities After Cardiac Surgery: Impact on Children’s Quality of Life and Parents’ Mental Health

Abstract: Background Most children now survive cardiac surgery, and the focus of quality improvement initiatives has shifted toward more complex outcome measures. The aim of this investigation was to study the impact of early postoperative morbidities on parent-reported patient quality of life and parental anxiety or depression over 6 months. Methods This prospective case-matched cohort study was conducted in 5 UK children’s cardiac centers. Measures of impact for patient categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…The cardiac impact study was designed to prospectively assess the impact of postoperative morbidities on patients and families 11 18. This phase of our study followed up children who had surgery in infancy, and found evidence that a very complex postoperative course with multiple morbidities/ECLS was linked to a greater chance of neurodevelopmental difficulties at age 2–3 years than those with no morbidity following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The cardiac impact study was designed to prospectively assess the impact of postoperative morbidities on patients and families 11 18. This phase of our study followed up children who had surgery in infancy, and found evidence that a very complex postoperative course with multiple morbidities/ECLS was linked to a greater chance of neurodevelopmental difficulties at age 2–3 years than those with no morbidity following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Children were recruited as morbidity cases to the ‘cardiac impact study’ if they experienced at least one important postoperative morbidity, as selected and defined previously 10. These morbidities (defined in our previous study)17 18 were: acute neurological event, unplanned re-intervention, feeding problems, renal replacement therapy, major adverse events, ECLS, necrotising enterocolitis, postsurgical infection and prolonged pleural effusion or chylothorax. We also recruited a similar sized control sample within each centre, consisting of children matched by measures of cardiac disease complexity and chronological age, who were identified at discharge after heart surgery as having experienced no morbidities 17 18.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations